„Przebudzenie” Kate Chopin, czyli „amerykańska Bovary”(?) - Michalski, Przemysław (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2019)
This article deals with the question of the so-called Bovarism in The Awakening, the famous novel written by Kate Chopin. When it was first published in 1899, it was universally condemned for its alleged obscenity, just like its French predecessor. It is true, however, that unlike Flaubert’s book, The Awakening did not find itself in the dock, faced with charges of immorality, but the hostile reviews condemned the novel to many decades of obscurity. In this article, I try to return to the question of parallels between the two novels, which can be seen on many levels. Some similarities concern both male and female characters, while others are to do with specific narrative decisions and solutions. The most conspicuous example of the latter is the suicidal death of both heroines.